VD_FINDINFO HC / 2021 / 298 vom 26. April 2021 - VD Tribunal cantonal (2021)
MESURE PROVISIONNELLE, ACTION EN RAISON DU TROUBLE DE LA POSSESSION, SERVITUDE | 730 CC, 737 CC, 928 CC, 261 CPC (CH), 318 al. 1 let. b CPC (CH)